Sub-7-second genotyping of single-nucleotide polymorphism by high-resolution melting curve analysis on a thermal digital microfluidic device. Issue 4 (19th January 2016) - Chen, Tianlan; Jia, Yanwei; Dong, Cheng; Gao, Jie; Mak, Pui-In; Martins, Rui P.
Abstract : A novel thermal digital microfluidic (T-DMF) device enables precise thermal modulation and pipelined measurement of multiple samples. Ultrafast DNA melting curve analysis is achieved in less than 7 seconds, with the resolution adequate for single-nucleotide discrimination. Abstract : We developed a thermal digital microfluidic (T-DMF) device enabling ultrafast DNA melting curve analysis (MCA). Within 7 seconds, the T-DMF device succeeded in differentiating a melting point difference down to 1.6 °C with a variation of 0.3 °C in a tiny droplet sample (1.2 μL), which was 300 times faster and with 20 times less sample spending than the standard MCA (35 minutes, 25 μL) run in a commercial qPCR machine. Such a performance makes it possible for a rapid discrimination of single-nucleotide mutation relevant to prompt clinical decision-making. Also, aided by electronic intelligent control, the T-DMF device facilitates sample handling and pipelining in an automatic serial manner. An optimized oval-shaped thermal electrode is introduced to achieve high thermal uniformity. A device-sealing technique averts sample contamination and permits uninterrupted chemical/biological reactions. Simple fabrication using a single chromium layer fulfills both the thermal and typical transport electrode requirements. Capable of thermally modulating DNA samples with ultrafast MCA, this T-DMF device has the potential for a wide variety of life science analyses, especially for disease diagnosis and prognosis.